The impact of part-time staff on Art & Design students' ratings of their programmes - Yorke, Mantz (Journal of higher education policy and management, 2014)
Art & Design receives ratings on a number of scales of the UK's National Student Survey (NSS) that are less strong than those for some other subject areas. Art & Design, along with performing arts, is characterised by a relatively high level of part-time (PT) staffing. PT staffing data are set against NSS ratings for post-92 universities and other institutions that specialise in studio-based programmes in Art & Design. The data from Art & Design are compared with data from selected subject areas, showing that for both Art & Design and performing arts higher levels of PT staffing are associated with lower NSS ratings. The quality of the available data and the implications of the analyses are discussed.